Tocopherol Enhances the Antioxidant Defense System and Histomorphometric Parameters in The Gastrointestinal Tract of Rats Treated with Sodium Arsenite (Nigerian Journal of Physiological Sciences, 2022)
Arsenic compromises the gastrointestinal integrity and function via the body's anti-oxidative system breakdown.  Hence, this study aimed to investigate the effects of tocopherol on redox imbalance and histoarchitectural alterations in rats' gastrointestinal tract exposed to sodium arsenite. Sodium arsenite and graded doses of tocopherol were administered orally into experimental rats assigned to different groups for four weeks concurrently. Redox status assay was done in homogenized samples by spectrophotometry. Parietal cell mass and mucous cell density (stomach), villus height and crypt depth (ileum), goblet cells count, and crypt depth (colon) were evaluated by histomorphometry. Inflammatory cells infiltration was also assessed using a semi-quantitative procedure. Sodium arsenite caused a significant increase in Malondialdehyde and Myeloperoxidase but, decreased Superoxide dismutase, Catalase, Nitric oxide, Glutathione peroxidase, Glutathione, and Glutathione-S-Transferase. Tocopherol treatment reversed the changes (p